Raising awareness about the importance of chickenpox vaccination in children - Borkowska, Aleksandra; Marosz, Szymon; Marosz, Karol; Chilimoniuk, Zuzanna; Sobstyl, Anna; Dudziński, Dominik; Chałupnik, Aleksandra; Krupska, Katarzyna; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2023)
Introduction: Varicella is an acute infectious disease caused by the Varicella zoster virus. It is among one of the most contagious infectious diseases. The main symptoms of the disease are an itchy, papular and vesicular rash on the trunk, face, scalp, extremities, mucous membranes. In addition, there is fever, malaise, headache and muscle aches, enlargement of lymph nodes. In most cases, varicella is mild, but 2-6% of patients may develop dangerous complications. The most common complications include bacterial skin infections, neurological symptoms and acute thrombocytopenia. Aim: The purpose of this study is to present the severe and complicated course of varicella in a 12-month-old patient. Results: On the day of admission, the patient presented symptoms of an exacerbation of the course of varicella. The main symptoms were smallpox eruptions, increasing fever track, and enlarged and painful lymph nodes. During his stay, the patient’s condition indicated a severe course of varicella. It was complicated by infection of the skin, subcutaneous tissue and lymph nodes. In addition, tests showed Epstein-Barr virus (EBV) infection and positivity for cat scratch disease. He also developed zoster during his hospitalization. Throughout his stay in the hospital, many tests and consultations were carried out to clarify his symptoms. With appropriate treatment, the patient’s condition improved and he was able to be discharged home after a 3-week hospitalization. Conclusions: The presented case shows the severe course of varicella. Due to recommendations and the patient’s too young age, he could not be vaccinated against VZV. In each patient, the course of the disease is unpredictable. Vaccination protects against severe symptoms, and also reduces the risk of developing zoster in the future. In addition, long-term immunity can be acquired through vaccination.